The Effect Of Mutual Fund Age And Mutual Fund Size On The Performance Of Equity Mutual Funds In 2015-2019 - Hertina, Dede; Bilal, Mochamad; Wirand, Ayunita Anggraeni (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to analyze the effect of mutual fund age and mutual fund size on the performance of equity funds. Mutual fund performance is measured by using the Sharpe Ratio. The age of the mutual fund is calculated based on the effective date the mutual fund is offered and the size of the mutual fund is calculated based on the amount of funds under management and the data used are the Net Asset Value (NAV) of the stock mutual fund, 15 equity mutual funds that were sampled with the research period during 2015-2019. This research method uses multiple linear regression test. The method used in testing the hypothesis is the T test. The results of the analysis show that the age of the mutual fund and the size of the equity fund have no effect on the performance of the equity fund.